Le Philèbe de Platon : introduction à l'agathologie platonicienne - Delcomminette, Sylvain. (Philosophia Antiqua, 2006)
This book deals with the nature and function of the good in Plato's philosophy, by focusing on the dialogue explicitly devoted to it: the Philebus. It provides a comprehensive commentary of this difficult dialogue in which almost all the themes of Plato's philosophy are discussed or alluded to. The author shows that a scrupulous analysis and reconstruction of its argumentative progress makes it possible to discover the unity between these different topics, and argues that this unity lies in the fact that Plato develops there what he was calling for notably in the Republic, id est a (dialectical) science of the good (or 'agathology'). Read from this viewpoint, the Philebus appears as a dialogue of tremendous importance for the understanding of Plato's philosophy as a whole.